2019
DOI: 10.1063/1.5086326
|View full text |Cite
|
Sign up to set email alerts
|

Eley Rideal recombination of hydrogen atoms on Cu(111): Quantitative role of electronic excitation in cross sections and product distributions

Abstract: Eley-Rideal (ER) reaction between a projectile and an adsorbate at a gas-surface interface represents many interesting dynamic features. Electron-hole pairs (EHPs) could play an important role in this process, given the interaction between the accelerated incident atom/molecule and the surface electrons. Here, we examine the EHP effects in a benchmark ER reaction of an impinging H/D atom and pre-covered D/H atoms on Cu(111) by ab initio molecular dynamics simulations. It is found that energy dissipation to EHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 63 publications
4
29
0
Order By: Relevance
“…Additionally, the optPBE-vdW 331 SRP-DF 150 was used successfully to model the abstraction of D by H or H by D from Cu (111) resulting in HD. 583 Specifically, the DFMDEF calculations using this SRP-DF showed quantitative agreement with experiments 666 concerning the abstraction cross section, the final rotational state and angular distributions of HD, and the final average E t of HD. The calculations also showed that modeling ehp excitation was necessary to reach a high level of agreement, which could be explained in terms of energy loss by the incident atom being more important for the hot atom reaction of the lighter (H) incident atom.…”
Section: Systems For Which Srp-dfs Have Been Derivedsupporting
confidence: 57%
See 3 more Smart Citations
“…Additionally, the optPBE-vdW 331 SRP-DF 150 was used successfully to model the abstraction of D by H or H by D from Cu (111) resulting in HD. 583 Specifically, the DFMDEF calculations using this SRP-DF showed quantitative agreement with experiments 666 concerning the abstraction cross section, the final rotational state and angular distributions of HD, and the final average E t of HD. The calculations also showed that modeling ehp excitation was necessary to reach a high level of agreement, which could be explained in terms of energy loss by the incident atom being more important for the hot atom reaction of the lighter (H) incident atom.…”
Section: Systems For Which Srp-dfs Have Been Derivedsupporting
confidence: 57%
“…74,582 DFMDEF calculations also addressed energy dissipation upon DC of H 2 on Pd(100). 74,114,582 Another topic addressed with DFMDEF is Eley-Rideal reactions, of H-atoms on Cu(111), 583 of D-atoms with CD 3 pre-adsorbed to Cu(111), 584 and of H with Cl preadsorbed to Au (111). 585 Finally, DFMDED calculations investigated scattering of N-atoms from Ag(111), 74,541,582 and dynamic displacement of CO pre-adsorbed to Cu (111) by incident H-atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the explicit construction of a PES can be avoided by running direct dynamics, where the forces acting on nuclei are computed on‐the‐fly during (quasi‐)classical trajectories. While this so‐called ab initio molecular dynamics (AIMD) method has been frequently applied in studying gas‐surface reactions, [ 36‐45 ] it remains very expensive for rare and/or long‐time events and is not our topic here. Indeed, recent neural network based methods have substantially accelerated the atomistic simulation of surface reaction dynamics, which can be now routinely studied beyond the Born‐Oppenheimer static surface approximation.…”
Section: Introductionmentioning
confidence: 99%